Influence of Modification of Pentasils with Alkaline-Earth Metals on Their Acid and Catalytic Properties in Conjugate Conversion of Methanol and Propane-Butane Fraction; Russian Journal of Applied Chemistry; Vol. 75, iss. 5 - Erofeev V. I. Vladimir Ivanovich; Shabalina L. B.; Koval' L. M.; Minakova T. S. (Catalysis, 2002)
Title screen